What is materialism? Testing two dominant perspectives on materialism in the marketing literature - Manchiraju Srikant; Krizan Zlatan (Management şi Marketing, 2015)
Materialism is defined as the importance an individual attaches to worldly possessions, which has been considered as an important construct in consumer behavior and marketing literature. There are two dominant perspectives on individual materialism in the marketing literature that focus on (1) personality traits or (2) individual personal values. However, several scholars have questioned the aforementioned materialism conceptualizations. Therefore, the present study directly compares the constructs of personality materialism and value materialism. Structural equation modeling was employed to address the following issues: (1) what are the key conceptual dimensions of materialism, (2) how much do they overlap, and (3) what is their discriminant validity in predicting outcomes linked to materialism. We suggest these two dominant perspectives on individual materialism are two distinct constructs, as they shared only 21 percent of common variance. Furthermore, we stress the multi-faceted nature of materialism, with an emphasis on future research directions related to materialism in marketing.